A bill to amend the Revised statutes, goncerning deeds and conveyances (House doc. (North Carolina. General Assembly. House of Commons) ;, 1852)
1852 North Carolina House bill to amend Chapter 27 of the Revised Statutes, entitled "Deeds and Conveyances. The changes established a method for requiring and registering any leases or powers of attorney longer than three years.